Statistical Literacy of University Students: An Analysis of Decision-Making, Evaluating, Communicating, and Interpreting Skills - Zulqoidi Habibie; Kartono` Kartono; Wardono; Iqbal Kharisudin (Hipotenusa: Journal of Mathematical Society, 2026)
This study aimed to analyze university students’ statistical literacy based on four indicators: decision-making, evaluating, communicating, and interpreting, as well as to examine differences in statistical literacy according to gender. A descriptive survey design was employed. The participants comprised 144 students from six universities across five provinces in Indonesia: Banten, Jakarta, East Java, Jambi, and Bengkulu, who were selected using non-probability sampling with a convenience sampling technique. Data were collected using an open-ended statistical literacy test developed based on response-skill indicators from the perspective of data consumers. The collected data were analyzed using descriptive statistics and the Mann–Whitney U test to determine whether significant differences existed between male and female students. The results revealed no statistically significant differences in statistical literacy between male and female students. Among the four indicators (decision-making (average 22.9), evaluation (75), communication (55.6), and interpretation (22.2)) students demonstrated relatively stronger performance in evaluating and communicating statistical information than in decision-making and interpreting. Analysis of students’ responses indicated that the main difficulties were related to understanding the context of statistical information, accurately interpreting data, integrating multiple statistical measures when making decisions, and effectively communicating information derived from graphs and datasets. These findings highlight the importance of integrating statistical knowledge with contextual understanding to support the development of statistical literacy among university students. The limitations of this study are evident in the data collected, namely the imbalance in the number of male and female students, which means the results cannot yet be generalized; further research is needed.